SECTM1 acts as an immune-related biomarker of poor prognosis and promotes cancer progression by modulating M2 macrophage polarization in esophageal squamous cell carcinoma - Pengzhou Kong; Pengzhou Kong; Pengzhou Kong; Ye Jiao; Ye Jiao; Meng Sun; Meng Sun; Zhinan Zhou; Zhinan Zhou; Yingying Zhang; Yingying Zhang; Xin Yang; et al. (Frontiers in Immunology)
Esophageal squamous cell carcinoma (ESCC) is the most prevalent primary malignant esophageal tumor in China and has a poor prognosis, but lacks effective diagnostic and prognostic biomarkers. Through single-sample gene set enrichment analysis (ssGSEA), we conducted immune genomic analysis based on 28 immune features using transcriptomic data from 155 ESCC cases. We established of two ESCC subtypes characterized by high and low immune profiles, and 352 differentially expressed immune genes were identified between the two subtypes. Performed with univariate and multivariate Cox regression, a novel prognostic prediction model was developed based on three immune-related genes (MAP3K8, SECTM1, IGLV7-43), which has been identified as a relatively accurate, independent, and specific prognostic risk model for ESCC patients in different ESCC cohorts. Furthermore, SECTM1 was upregulated in ESCC tissues and associated with adverse clinical outcomes. In cell experiments, overexpression of SECTM1 effectively promoted the proliferation, migration, and invasion of ESCC cells, while SECTM1 knockdown significantly inhibited these cellular processes. Furthermore, its overexpression promoted macrophage polarization towards the M2-like phenotype and promoted the migration of M2-like macrophage cells and C-C Motif Chemokine Ligand 5 (CCL5) was the key mediator in the pro-cancer effect of SECTM1. In a Conclusion, our study established a prognostic prediction model based on immune-related gene signature, which provided a reliable prognostic tool for ESCC and identified SECTM1 as a potential biomarker in ESCC.